Sibu Island local community’s perception towards the establishment of Marine Park Areas - Fatimah, K; NurulHuda, S. (University Kebangsaan Malaysia, 2012)
This paper aims at examining the acceptability and perception of local communities in Sibu Island towards the Marine Park Conservation policy. Information on acceptability and locals’ attitudes towards the conservation efforts contributes to our understanding on the effectiveness of MPA policies for the successful implementation of conservation policies depend largely on the readiness and willingness of local communities to participate in such program. We found that Sibu Island community members show high degree of understanding on the conservation regulations and also willingness to support and participate in conservation activities. These findings suggest a satisfactory degree of acceptability among local community members. We also found that the acceptability index is influenced by education level. A comparison made between Sibu, Redang, and Tioman islands suggest that the acceptability of Sibu island community members is relatively higher compared to Redang Island. We attribute this difference to the differences in economic conditions between these islands.